Exercise as a Mean to Control Low-Grade Systemic Inflammation - Neha Mathur; Bente Klarlund Pedersen (Mediators of Inflammation)
Chronic noncommunicable diseases (CNCDs), which include cardiovascular disease, some cancers, for example, colon cancer, breast cancer, and type 2 diabetes, are reaching epidemic proportions worldwide. It has now become clear that low-grade chronic inflammation is a key player in the pathogenesis of most CNCDs. Given that regular exercise offers protection against all causes of mortality, primarily by protection against atherosclerosis and insulin resistance, we suggest that exercise may exert some of its beneficial health effects by inducing anti-inflammatory actions. Recently, IL-6 was introduced as the first myokine, defined as a cytokine, which is produced and released by contracting skeletal muscle fibres, exerting its effects in other organs of the body. We suggest that skeletal muscle is an endocrine organ and that myokines may be involved in mediating the beneficial effects against CNCDs associated with low-grade inflammation.